Connectors for electrical and electronic equipment. Tests and measurements. Additional specifications for signal integrity tests up to 2 000 MHz on IEC 60603-7 series connectors. Tests 27a to 27g Part 27-200, (25th October 2022) - British Standards Institution,
No abstract available